2004
DOI: 10.1210/en.2004-0371
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Olive Oil and Menhaden Oil Mitigate Induction of Lipogenesis in Hyperinsulinemic Corpulent JCR:LA-cp Rats: Microarray Analysis of Lipid-Related Gene Expression

Abstract: In the corpulent James C. Russell corpulent (JCR:LA-cp) rat, hyperinsulinemia leads to induction of lipogenic enzymes via enhanced expression of sterol-regulatory-binding protein (SREBP)-1c. This results in increased hepatic lipid production and hypertriglyceridemia. Information regarding down-regulation of SREBP-1c and lipogenic enzymes by dietary fatty acids in this model is limited. We therefore assessed de novo hepatic lipogenesis and hepatic and plasma lipids in corpulent JCR rats fed diets enriched in ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 79 publications
5
26
2
1
Order By: Relevance
“…In this way, substitution of dietary monounsaturated or polyunsaturated fatty acid (olive oil and menhaden oil) for carbohydrate reduced hepatic expression of SREBP-1c, with concomitant reductions in hepatic triglyceride content, lipogenesis, and expression of enzymes related to lipid synthesis in corpulent James C. Russell (JCR:LA-cp) rats. Unexpectedly, this substitution increased expression of many peroxisomal proliferator-activated receptor-dependent enzymes mediating fatty acid oxidation [61]. Olive substitution for butter (10% of total energy) for two weeks modulated several genes related to lipolysis or lipogenesis in normal rats [62] and newly identified genes from other metabolisms ( Fsp27 and Syt1 ) in apoE-deficient mice [65].…”
Section: Effect Of Dietary Fat Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, substitution of dietary monounsaturated or polyunsaturated fatty acid (olive oil and menhaden oil) for carbohydrate reduced hepatic expression of SREBP-1c, with concomitant reductions in hepatic triglyceride content, lipogenesis, and expression of enzymes related to lipid synthesis in corpulent James C. Russell (JCR:LA-cp) rats. Unexpectedly, this substitution increased expression of many peroxisomal proliferator-activated receptor-dependent enzymes mediating fatty acid oxidation [61]. Olive substitution for butter (10% of total energy) for two weeks modulated several genes related to lipolysis or lipogenesis in normal rats [62] and newly identified genes from other metabolisms ( Fsp27 and Syt1 ) in apoE-deficient mice [65].…”
Section: Effect Of Dietary Fat Contentmentioning
confidence: 99%
“…Induction of SREBP-1c by insulin was dependent on LXR α . Expression of mRNA encoding fatty acid translocase and ATP-binding cassette subfamily DALD member 3 was also increased in livers of corpulent JCR rats, indicating a potential role for these fatty acid transporters in the pathogenesis of disordered lipid metabolism in obesity [61]. …”
Section: Effect Of Dietary Fat Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic lipid levels and liver lipid metabolism-related gene expression were affected by the WO and FO diets, but the effects were more marked in the latter case. In previous studies it was demonstrated that oleic acid inhibits fatty acid synthesis-related gene expression and enhances PPARα target gene expression in the liver [31][32][33]. In the experimental diets used in this study, the oleic acid content was higher in the FO diet than in the WO diet (Table 2).…”
Section: Discussionmentioning
confidence: 59%
“…Muscle wasting is a well recognized adverse event of excess glucocorticoids caused by both increased muscle proteolysis and decreased protein synthesis (Deng et al 2004, Menconi et al 2007. Exposure of rats to glucocorticoids activates the muscle ubiquitin-proteasome system (Wing & Goldberg 1993, Price et al 1994, increasing muscle expression of proteases (cathepsins B and D, calpain) and components of the ubiquitin-proteasome pathway (Dardevet et al 1995) along with the inhibition of muscle protein synthesis (Long et al 2001).…”
Section: Discussionmentioning
confidence: 99%